Substituted acyl thioureas and acyl thiosemicarbazides: synthesis and biological activity (minireview) - Kholodniak, Olena; Kovalenko, Sergiy (ScienceRise: Pharmaceutical Science, 2022)
Acyl isothiocyanates and their functional derivatives (acyl thioureas and acyl thiosemicarbazides) are an important group of organic compounds that are widely used in the synthesis of heterocycles and in chemistry as catalysts, ligands, colorimetric hemosensors, etc. In recent years, there has been an increased interest towards this class of compounds as promising biologically active compounds, especially since the latest advances in medicinal chemistry for them are not sufficiently studied. The aim. To summarize and systematize information for the last 10 years on methods of synthesis and biological activity of substituted acyl thioureas and acyl thiosemicarbazides. Materials and methods. Web-tools for finding scientific information (Reaxys, Scopus, Google Scholar, ScienceResearch, SciFinder, Web of Science, etc.). Results and discussion. Literature sources related to the methods of synthesis of substituted acyl thioureas and acyl thiosemicarbazides were systematized and analyzed. The main approaches for the formation of these compounds are revealed: stepwise formation from carboxylic acids, through acyl chlorides and acyl isothiocyanates followed by nucleophilic addition of amines or hydrazides of carboxylic acids ("one-pot synthesis"), nucleophilic addition of amines or hydrazides of carboxylic acids directly to acyl isothiocyanates and parallel microwave synthesis using acyl isothiocyanates and amines as reagents. The possibility of their use as ligands for the formation of complex compounds with transition metal ions was discussed. In the review biological activity of these structures, namely antimicrobial, fungicidal, antitumor, antiviral, antifungal and other activities was detailazed. Conclusions. The basic approaches to the synthesis of substituted acylthuoureas and acyl thiosemicarbazides which include the application of carboxylic acids, their derivatives (acyl halides and isothiocyanates) and N-nucleophiles as initial compounds were discussed. It was shown that aforementioned class of the compounds reveals the versatile biological activity and are promising for further structural modification aimed to the search of novel drugs